2015
DOI: 10.1080/23249676.2015.1090353
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the scour cavity evolution around a complex bridge pier

Abstract: A study on the time development of local scour around a complex pier was developed using a small-scale model embedded in a sediment bed. A total of 15 laboratorial tests were performed at the Hydraulics Laboratory of the Faculty of Engineering of the University of Porto. The duration of each experiment was previously established to progressively characterize the scour cavity. After each experiment, the flume was gradually emptied to facilitate the application of closerange photogrammetry. The scour depth value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…SfM techniques have already been used and tested in a wide array of field applications (e.g., Westoby et al, 2012;Fonstad et al, 2013;Micheletti et al, 2015), but few studies have used SfM in a laboratory setting (Marra et al, 2014;Kasprak et al, 2015;Ramos et al, 2015;Wang et al, 2016). This technology is becoming increasingly popular, but to our knowledge there have been no studies explicitly evaluating the relative performance of SfM against other methods of topographic measurement in a laboratory flume environment (but see Nouwakpo et al 2014), and there is a general lack of guidelines for SfM application in flume settings.…”
Section: Introductionmentioning
confidence: 99%
“…SfM techniques have already been used and tested in a wide array of field applications (e.g., Westoby et al, 2012;Fonstad et al, 2013;Micheletti et al, 2015), but few studies have used SfM in a laboratory setting (Marra et al, 2014;Kasprak et al, 2015;Ramos et al, 2015;Wang et al, 2016). This technology is becoming increasingly popular, but to our knowledge there have been no studies explicitly evaluating the relative performance of SfM against other methods of topographic measurement in a laboratory flume environment (but see Nouwakpo et al 2014), and there is a general lack of guidelines for SfM application in flume settings.…”
Section: Introductionmentioning
confidence: 99%
“…it develops almost linearly if time is put in the logarithmic scale [43][44][45]. Recent studies nevertheless demonstrated that for protected piers (tests T1 and T2) scour develops through various stages at different rates, depending on the initially landfilled geometry that gradually emerges [33,[46][47][48]. Figure 4 shows the temporal evolution of d s for all tests.…”
Section: Results and Discussion (A) Laboratory Experimentsmentioning
confidence: 99%
“…Numerous experimentalists have adapted the method to the remote sensing of model topography, most commonly with convergent cameras mounted on a rolling instrument cart above the experiment. Laboratory 'SfM' has been used to monitor experiments with braided rivers (Javernick et al, 2018;Kasprak et al, 2015;Leduc et al, 2019;Middleton et al, 2019;Peirce et al, 2018Peirce et al, , 2019, alluvial fans and steep unconfined flows (Leenman & Eaton, 2021;Leenman et al, 2022;Piton et al, 2018;Vincent et al, 2022), estuaries (Braat et al2019;Leuven et al, 2018), step-pool channels (Wang et al, 2021;Zhang et al, 2020), Martian valley evolution , bridge scour (Ramos et al, 2016), bedforms (Adams & Zampiron, 2020;Bankert & Nelson, 2018;Nelson & Morgan, 2018;Polvi, 2021), alluvial cover (Buechel et al, 2022;Papangelakis et al, 2021;Welber et al, 2020), and the effects of plants and wood (Spreitzer et al, 2020b(Spreitzer et al, , 2021Wang et al, 2016).…”
Section: Dye-based Planform Trackingmentioning
confidence: 99%